MOTIVASI PESERTA EKSTRAKURIKULER FUTSAL PUTRI DI SMK NEGERI 5 PONTIANAK - Tommy, Tommy; Purnomo, Edi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMotivation is defined as a sense of preferability and interest in a thing or activity, without anyone asking. To achieve this goal, the schools in SMPN 5 Pontianak are able to be involved in futsal extracurricular activities as students' interest in participating in sports extracurricular activities.This study aims to determine how high the interest of students in participating in futsal extracurricular activities at SMPN 5 Pontianak sport, The research design used in this research is quantitative descriptive survey method with data collection techniques using, questionnaire. The population in this study were students who took futsal extracurricular totaling 30 total sampling.The results showed that students' interest in participating in futsal extracurricular activities in SMPN 5 pontaianak as many as 30 students (66%) had high interest and futsal extracurricular categories were high, as many as 10 (44%) meaning that this extracurricular needs to be appropriately and accurately accommodated students accommodated their talents and interests.Â Keywords: Student Motivation, Extracurricular Futsal